Thirty years of blackouts: a case report of swallow syncope - Irene Lambiris; Ivan Mendoza; Marcelo Helguera; Jose Baez Escudero; Cesar Bonilla (Greater Baltimore Medical Center, 2013)
Deglutition syncope has been demonstrated in isolated case reports, the first being described over 50 years ago. It is thought to be caused by a hypersensitive vagotonic reflex in response to esophageal dilation after swallowing. It can cause syncope due to complete atrioventricular (AV) block and acute reduction of cardiac output. Although rare, its lethality is worthy of discussion, as early recognition can offer complete treatment with placement of a pacemaker. A 54-year-old man presented with 30 years of lightheadedness and syncope, followed by disorientation and tremors, after eating sandwiches or drinking carbonated beverages. He initially was evaluated by a neurologist. Work-up included cardiac 2D transthoracic echocardiogram, electroencephalogram, swallow stud, pulmonary function tests, electrocardiogram, and cardiac stress testing. All tests were within normal limits, and it was determined that he was suffering from convulsive syncope and deglutition syncope. Referral to the cardiac electrophysiology department with tilt-table testing accompanied by swallow evaluation was then recommended. The tests demonstrated marked vagal response resulting in sinus bradycardia with second-degree AV block and pauses up to 3.5 seconds. Patient experienced near syncope. A rate-responsive, dual-chamber Boston Scientific pacemaker with DDDR programming was implanted. Patient has remained asymptomatic at follow-up.